Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1523/jneurosci.1885-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Hypothalamic Area Controls Paradoxical (REM) Sleep by Means of Descending Projections to Brainstem GABAergic Neurons

Abstract: It has recently been shown that the ventrolateral part of the periaqueductal gray (VLPAG) and the adjacent dorsal deep mesencephalic nucleus (dDpMe) contain GABAergic neurons gating paradoxical sleep (PS) onset by means of their projection to the glutamatergic PS-on neurons of the sublaterodorsal tegmental nucleus (SLD). To determine the mechanisms responsible for the cessation of activity of these GABAergic PS-off neurons at the onset and during PS, we combined the immunostaining of c-FOS, a marker of neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 56 publications
4
73
0
Order By: Relevance
“…The SLD and PC are held in check by inhibitory inputs from the ventrolateral periaqueductal gray matter (vlPAG) and adjacent lateral pontine tegmentum (LPT, also called the deep mesencephalic nucleus) (Lu et al, 2006, Vetrivelan et al, 2011, Luppi et al, 2012). Both the REM-On (SLD/PC/LDT/PPT) and the REM-Off (vlPAG/LPT) structures receive intense MCH input (Torterolo et al, 2009, Clement et al, 2012, Torterolo et al, 2013), as does the ventrolateral medullary (vM) area (Bittencourt et al, 1992) where Weber and colleagues have recently identified GABAergic neurons that generate REM sleep by inhibiting the vlPAG/LPT (Weber et al, 2015). Thus, MCH neurons are likely to regulate REM sleep by inhibiting the vlPAG/LPT and activating the SLD/PC/LDT/PPT/vM, although the physiology of these connections remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLD and PC are held in check by inhibitory inputs from the ventrolateral periaqueductal gray matter (vlPAG) and adjacent lateral pontine tegmentum (LPT, also called the deep mesencephalic nucleus) (Lu et al, 2006, Vetrivelan et al, 2011, Luppi et al, 2012). Both the REM-On (SLD/PC/LDT/PPT) and the REM-Off (vlPAG/LPT) structures receive intense MCH input (Torterolo et al, 2009, Clement et al, 2012, Torterolo et al, 2013), as does the ventrolateral medullary (vM) area (Bittencourt et al, 1992) where Weber and colleagues have recently identified GABAergic neurons that generate REM sleep by inhibiting the vlPAG/LPT (Weber et al, 2015). Thus, MCH neurons are likely to regulate REM sleep by inhibiting the vlPAG/LPT and activating the SLD/PC/LDT/PPT/vM, although the physiology of these connections remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…MCH, when injected intracerebroventricularly, produces a robust (~200%) increase in REM sleep (Verret et al, 2003) while infusion of an MCH receptor antagonist causes a significant reduction in REM sleep in rats (Ahnaou et al, 2008). MCH neurons heavily innervate the dorsolateral brainstem regions implicated in REM generation including the sublaterodorsal nucleus (SLD) and ventrolateral periaqueductal gray matter (vlPAG), (Hanriot et al, 2007, Peyron et al, 2009, Sapin et al, 2010, Clement et al, 2012) and local injection of MCH into the nucleus pontis oralis (in the subcoeruleus region which is considered to be an SLD-equivalent in cats) produces a significant increase (~70%) in REM sleep and reduces the latency to REM sleep (Torterolo et al, 2009). Juxtacellular recording studies show that MCH neurons are maximally active during REM sleep, silent during wake, and occasionally active in NREM sleep (Hassani et al, 2009), suggesting that they promote REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that the ACC/PLC innervates MCH and orexin neurons in the lateral hypothalamus. MCH neurons are active during REM sleep (Verret et al, 2003; Hassani et al, 2009), and send inhibitory projection to the vlPAG/LPT (Clement et al, 2012). We have found that at least some of the MCH neurons are active in proportion to the amount of cataplexy, suggesting that they may also help inhibit the vlPAG/LPT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that the periaqueductal gray (PAG) and the rostral ventromedial medulla (RVM) constitute the outflow of descending modulation and that peripheral damage can alter the balance between inhibition and facilitation of nociception by these brainstem structures (Niesters et al, 2013; De Felice et al, 2011; Heinricher et al, 2009; Vanegas and Schaible, 2004). The LH sends projections to both the PAG (Clement et al, 2012; Hsieh et al, 2011; Holden et al, 2009) and RVM (Barba, et al, 2014; Holden et. al., 2005; Herman, et al, 1997) as well as the descending noradrenergic neurons in the dorsolateral pontine tegmentum (Tokita et al, 2009; Holden and Naleway, 2000; Holden, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%